Fractional exhaled nitric oxide as a predictor of response to inhaled corticosteroids in patients with non-specific respiratory symptoms and insignificant bronchodilator reversibility: a randomised controlled trial. Issue 1 (January 2018) - Price, David B; Buhl, Roland; Chan, Adrian; Freeman, Daryl; Gardener, Elizabeth; Godley, Clifford; Gruffydd-Jones, Kevin; McGarvey, Lorcan; Ohta, Ken; Ryan, Dermot; Syk, Jörgen; Tan, Ngiap Chuan; et al.
Summary: Background: Chronic non-specific respiratory symptoms are difficult to manage. This trial aimed to evaluate the association between baseline fractional exhaled nitric oxide (Fe NO) and the response to inhaled corticosteroids in patients with non-specific respiratory symptoms. Methods: In this double-blind randomised placebo-controlled trial, we enrolled undiagnosed patients, aged 18–80 years, with cough, wheeze, or dyspnoea and less than 20% bronchodilator reversibility across 26 primary care centres and hospitals in the UK and Singapore. Patients were assessed for 2 weeks before being randomly assigned (1:1) to 4 weeks of treatment with extrafine inhaled corticosteroids (QVAR 80 μg, two puffs twice per day, equivalent to 800 μg per day beclomethasone dipropionate) or placebo. Randomisation was stratified by baseline Fe NO measurement: normal (≤25 parts per billion [ppb]), intermediate (>25 tp <40 ppb), and high (≥40 ppb). The primary endpoint was change in Asthma Control Questionnaire (ACQ7) mean score. We used generalised linear modelling to assess Fe NO as a predictor of response, estimating an interaction effect between Fe NO and treatment on change in ACQ7. We did our primary and secondary analyses in the per-protocol set, which excluded patients with non-completion of the primary endpoint, non-compliance to treatment (ascertained by patient report), and study visits made outside the predefined visit windows. This study is registered onClinicalTrials.gov, numberNCT02294279 . Findings: Between Feb 4, 2015, and July 12, 2016, we randomly assigned 294 patients to extrafine inhaled corticosteroid treatment (n=148) or placebo (n=146). Following exclusions due to protocol violations, we analysed 214 patients (114 extrafine inhaled corticosteroids and 100 placebo). We observed a significant interaction between baseline Fe NO and treatment group for every 10 ppb increase in baseline Fe NO, with the change in ACQ7 greater in the extrafine inhaled corticosteroids group than in the placebo group (difference between groups 0·071, 95% CI 0·002 to 0·139; p=0·044). The most common adverse events were nasopharyngitis (18 [12%] patients in the treatment group vs 13 [9%] in the placebo group), infections and infestations (25 [17%] vs 21 [14%]), and respiratory, thoracic, and mediastinal disorders (13 [9%] vs 17 [12%]). Interpretation: Fe NO measurement is an easy and non-invasive tool to use in clinical practice in patients with non-specific respiratory symptoms to predict response to inhaled corticosteroids. Further research is needed to examine its role in patients with evidence of other airway diseases, such as chronic obstructive pulmonary disease. Funding: Sponsored by OPRI with partial funding by Circassia and study drugs provided by TEVA.